2012
DOI: 10.12693/aphyspola.121.217
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Indium-Doped Zinc Oxide Thin Films Prepared by Sol-Gel Method

Abstract: Indium-doped ZnO thin films were deposited by sol-gel spin-coating method with various In content. The effects of In content on the structural and optical properties of the indium-doped ZnO thin films were investigated by scanning electron microscopy, X-ray diffraction, and UV-visible spectroscopy. The particle-like surface morphology and the crystallinity of the indium-doped ZnO thin films were affected by change in the In content, especially at the In content of 3 at.%. The values of direct band gap were dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…2a). The red shift of the band gap of the ZnO film induced by In doping is consistent with previous reports [24,39,40] and can be explained by the variation of the Urbach energy, E U [41]. Urbach energy can be calculated using the following formula: Figure 3 shows the Urbach plot of ZnO thin films with different In-doping levels.…”
Section: Resultssupporting
confidence: 87%
“…2a). The red shift of the band gap of the ZnO film induced by In doping is consistent with previous reports [24,39,40] and can be explained by the variation of the Urbach energy, E U [41]. Urbach energy can be calculated using the following formula: Figure 3 shows the Urbach plot of ZnO thin films with different In-doping levels.…”
Section: Resultssupporting
confidence: 87%
“…The energy band widening of BZO thin films is common phenonmenon and reported in the previous studies [35][36][37]. The shift in the optical band gap is because of the Burstein-Moss shift and the energy band widening (blueshift) effect resulting from the increase in the Fermi level of the conduction bands of degenerate semiconductors [33,38,39]. The donor electrons in the doped semiconductors occupy states at the bottom of the conduction band.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, the decrease in the transmittance of the thin film doped with 2.5 at.% B might be attributed to the fact that the higher concentration of B increased the number of ionized impurity in the thin films, thus increasing the degree of light scattering in the thin films. The absorption coefficient (a) for a direct-transition semiconductor material obeys the following relation with respect to the optical band gap (E g ) [33,34]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of the blue shift depended on both indium content and vacuum annealing. A recent report [22] on spin-coated (IZO) films has shown that the values of direct band gap decreased with increase in the In content.…”
Section: Electrical Propertiesmentioning
confidence: 98%